Out-patient drug treatment of pneumonia among children under two years of age in Fortaleza, Brazil - Chizuru Misago; Tom F. Marshall; Walter Fonseca; Betty R. Kirkwood
Results are reported from a study on drug use in treatment of children with pneumonia in a pediatric hospital in the city of Fortaleza, Northeastern Brazil. There were 171 out-patients; prescription details were obtained for 149. The most commonly prescribed antimicrobial drug was procaine penicillin, accounting for 33% of antimicrobial prescriptions, followed by benzathine penicillin (31%), ampicillin or amoxicillin (12%), and cotrimoxazole (8%). Benzathine penicillin was frequently given with other drugs, but was the sole antimicrobial agent for 31 children. Compliance with antimicrobial treatment was 52% overall and was higher for the injectables. Prescription patterns varied from child to child, and children were often prescribed more than one antimicrobial in the same or repeat prescriptions; combining this information with compliance, 81 (54%) of the children were estimated to have received 5 or more days of appropriate antimicrobial treatment for pneumonia. This percentage is not high, and five days were often reached after using more than one antimicrobial and after repeat visits. The authors concluded that the need remains for simple antimicrobial regimes, attractive to comply with, that can be expected to be consistently used. Other drugs were chiefly analgesics and bronchodilators.